2019
DOI: 10.1111/cid.12771
|View full text |Cite
|
Sign up to set email alerts
|

The All‐on‐4 concept for full‐arch rehabilitation of the edentulous maxillae: A longitudinal study with 5‐13 years of follow‐up

Abstract: Background: Full-arch immediate function protocols such as the All-on-4 concept need long-term validation.Purpose: To report the 5-13 year outcomes of the All-on-4 treatment concept for the rehabilitation of the edentulous maxilla. Materials and Methods: This retrospective case series study involved 1072 patients (4288 maxillary implants) rehabilitated through the All-on-4 treatment concept. Primary outcome measures were cumulative prosthetic and implant success (life table analysis). Secondary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
5
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 36 publications
4
68
5
5
Order By: Relevance
“…Our study showed that 11% of all implants were lost over time (representing 89% implant success rate). The finding is lower than some of previous 10‐year follow‐up success rates (93%, 95.5%, or 93‐96.9%), which needs future investigation. However, the observed implant success rate falls between rates observed in other previous studies .…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Our study showed that 11% of all implants were lost over time (representing 89% implant success rate). The finding is lower than some of previous 10‐year follow‐up success rates (93%, 95.5%, or 93‐96.9%), which needs future investigation. However, the observed implant success rate falls between rates observed in other previous studies .…”
Section: Discussioncontrasting
confidence: 72%
“…No significant differences were observed between failure‐free survival rates of all‐resin and PFZ prostheses. The recent literature shows two different trends in long‐term survival rates of acrylic prostheses—high prostheses survival rates in 10‐ to 18‐years follow‐up study (99.6%), 94.8% at 10 years, 99.2 % at 13 years . On the other hand are studies reporting lower survival rates, such as (82%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal effectiveness of the MR IFCDPs against maxillary complete dentures has been demonstrated in the literature, with considerably high rates of technical complications like wear and chipping encountered as a result of material fatigue and stress . Studies have also reported on the incidence of complications with ceramic type IFCDPs . While no studies have been identified directly comparing intra‐group ceramic IFCDPs to MR IFCDPs, it must be mentioned that there is paucity of reports on complications with ceramic IFCDPs for edentulous jaws with observation periods of at least 5 years conversely with the MR design …”
Section: Discussionmentioning
confidence: 99%
“…The All-on-4 treatment concept consists of an immediate function rehabilitation protocol for full-arch rehabilitation of edentulous arches with insertion of four implants in the anterior region (two axial implants inserted anteriorly and two distally tilted posterior implants) to support a fixed prosthesis [1,2]. This concept was further developed to include the use of zygomatic implants alone or in combination with standard implants in situations of extreme maxillary resorption (All-on-4 Extra-maxilla or All-on-4 Hybrid) [3,4].…”
Section: Introductionmentioning
confidence: 99%